The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.stemcr.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correction of SOD1 Mutant iPSCs Reveals ERK and JNK Activated AP1 as a Driver of Neurodegeneration in Amyotrophic Lateral Sclerosis

Abstract: SummaryAlthough mutations in several genes with diverse functions have been known to cause amyotrophic lateral sclerosis (ALS), it is unknown to what extent causal mutations impinge on common pathways that drive motor neuron (MN)-specific neurodegeneration. In this study, we combined induced pluripotent stem cells-based disease modeling with genome engineering and deep RNA sequencing to identify pathways dysregulated by mutant SOD1 in human MNs. Gene expression profiling and pathway analysis followed by pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 49 publications
12
83
2
Order By: Relevance
“…2i). Deficiency in the mitochondrial oxidative phosphorylation pathway as well as suppression of translation secondary to ER stress with concomitant increase in cell cycle related genes has been identified previously in bulk analysis of ALS SOD1 MN(19), which was recapitulated in our single cell expression analysis. Importantly, dysregulation of synaptic signalling and structure in our ALS model supports the dying back hypothesis of ALS that posits neuronal degeneration is secondary to pathology initiated at the distal end of the axon and neuromuscular junction(32).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…2i). Deficiency in the mitochondrial oxidative phosphorylation pathway as well as suppression of translation secondary to ER stress with concomitant increase in cell cycle related genes has been identified previously in bulk analysis of ALS SOD1 MN(19), which was recapitulated in our single cell expression analysis. Importantly, dysregulation of synaptic signalling and structure in our ALS model supports the dying back hypothesis of ALS that posits neuronal degeneration is secondary to pathology initiated at the distal end of the axon and neuromuscular junction(32).…”
Section: Resultssupporting
confidence: 71%
“…We previously developed an in vitro model of ALS MN degeneration where MN differentiated from mutant SOD1 iPSC display disease-specific phenotypes such as reduced cell survival and morphometric defects compared to their isogenic control counterparts(19). We differentiated iPSC derived from patients bearing the SOD1 E100G mutation, as well as the corresponding CRISPR edited isogenic control into MN (Fig.1a) (19). Mature MN appeared by day 30 and expressed MN markers such as ISL1, CHAT and NF-H in addition to the pan-neuronal markers TUJ1 and MAP2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MAPKs and GSK3 are implicated in proper SG function and disease. For instance, aberrant MAPK p38 activity induces a gain of function for the ALS-linked SG component FUS (65), and, conversely, inhibition of MAPK signaling improves survival of SOD1 E100G mutant motor neurons derived from ALS patient induced pluripotent stem cells (66). Likewise, tight regulation of GSK3 activity appears to underlie proper SG responses, given that GSK3 inhibition dramatically reduces stress granule formation (12,67), and aberrant activation of GSK3 is associated with ALS (68).…”
Section: Phosphorylation Of Gle1a Regulates Ddx3 and Stress Responsementioning
confidence: 99%
“…Until now, variants on SOD1 gene have deeply been studied from patient-derived iPS cells using CRISPR-Cas9 nucleases. Comparison studies between MNs differentiated from ALS patient-derived iPS cells and MNs from SOD1 gene corrected cell lines revealed that functional changes by SOD1 mutations induce neurodegeneration and aberrant gene expression, resulting in vulnerable oxidative stress, altered protein response pathway, ER stress, and mitochondrial defect [26][27][28] . In more than 80% of ALS cases, however, the responsible genes for ALS still remain unclear [29][30][31] .…”
mentioning
confidence: 99%